2005
DOI: 10.1542/peds.2004-1336
|View full text |Cite
|
Sign up to set email alerts
|

Group A Streptococcal Subdural Empyema as a Complication of Varicella

Abstract: ABSTRACT. Group A ␤-hemolytic streptococcus and Staphylococcus aureus are the 2 most common pathogens implicated in secondary invasive bacterial disease after varicella. We describe a 3-month-old male infant from British Columbia, Canada, who presented on day 5 of varicella skin rash with fever, seizures, lethargy, and evidence of intracranial hypertension. A prominent subdural empyema was documented, and Streptococcus pyogenes was recovered from the subdural fluid. Central nervous system bacterial complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The portal of entry for invasive group A streptococcal disease (GAS) disease remains undetermined for about one-fourth of S. pyogenes 2. In the same review, among children and adults with confirmed GAS meningitis, two children were found to have brain abscess, two had subdural hygromas and none had SDE 2. From our literature search, we found no cases of SDE resulting from S. pyogenes originating from an acute pharyngeal infection.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The portal of entry for invasive group A streptococcal disease (GAS) disease remains undetermined for about one-fourth of S. pyogenes 2. In the same review, among children and adults with confirmed GAS meningitis, two children were found to have brain abscess, two had subdural hygromas and none had SDE 2. From our literature search, we found no cases of SDE resulting from S. pyogenes originating from an acute pharyngeal infection.…”
Section: Discussionmentioning
confidence: 88%
“…Her blood, CSF and surgically evacuated fluid cultures all grew S. pyogenes , with the suspected source being streptococcal pharyngitis based on oropharyngeal examination, despite negative previous testing. Intracranial infections caused by S. pyogenes are rare and nearly always associated with significant meningitis or a contiguous focus 2 3 8. In a review of SDE and its management, S. pyogenes is listed as a source for infection for SDE only when originating from either the paranasal sinuses, otomastoiditis or acute otitis media 2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations